PENGARUH AKTIVITAS BELAJAR TERHADAP HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN METODE SCAFFOLDING - Dewi, Lus Viana; Ahied, Mochammad; Rosidi, Irsad; Munawaroh, Fatimatul (Universitas Tanjungpura, 2019)
The aims of this research were to know the effect activity learning to student learning outcomes used model Discovery Learning with Scaffolding method and outcomes at the material of light. This is research an experimental study with the research design Pre-Experimental. The population this research is student VIII class in State Junior High School 1 Kamal. The sampling technique was purposive sampling. Sampling used VIII-I as many 36 students as experimental class. Technique of analyzing data use simple regression with program SPSS version 18.00. Based on the result of this research, it can be concluded that: there was an effect activity learning to student learning at sig was 0,030, because sig 0.05 so H0 rejected with regression equation Y